Maternal effects, flight versus fecundity trade-offs, and offspring immune defence in the Speckled Wood butterfly, Pararge aegeria - Hails Rosemary S; Hesketh Helen; Breuker Casper J; Gibbs Melanie; Van Dyck Hans (BMC Evolutionary Biology, 2010)
Abstract Background Maternal condition can generate resource-related maternal effects through differential egg provisioning, and can greatly affect offspring performance. In the present study, the speckled wood butterfly Pararge aegeria (L.) was used to investigate whether (after controlling for egg size) maternal age, and increased flight during the oviposition period, resulted in changes in egg provisioning and whether this contributed to variation in offspring performance, i) early in development (egg stage and early post-hatching development), and ii) later in larval development after being exposed to the model viral pathogen system; the baculovirus Autographa californica multinucleocapsid nucleopolyhedrovirus (AcMNPV). Results Age-related changes in maternal egg provisioning were observed to influence egg stage development only. Flight-induced changes in maternal egg provisioning had direct consequences for offspring growth and survival across each life stage from egg to adulthood; offspring from forced flight mothers had lower larval masses and longer development times. Offspring with lower larval masses also had reduced survival after exposure to the viral pathogen. Conclusion The present study demonstrates that a change in maternal provisioning as a result of increased flight during the oviposition period has the potential to exert non-genetic cross-generational fitness effects in P. aegeria. This could have important consequences for population dynamics, particularly in fragmented anthropogenic landscapes.